The tale of Hansuli Turn - Bandyopādhyāẏa, Tārāśaṅkara, 1898-1971 (Columbia University Press, 2011)
The Kahars of Hansuli Turn, a rural village in West Bengal, belong to an untouchable "criminal tribe" epically transformed during India's independence. Negotiating the colonial depredations of the 1939-45 war and the oppressions of an agrarian caste system, the Kahars might seem to welcome modernization, but many in the tribe fear the consequences of a revolutionized society and the loss of their culture within it. Lyrically rendered by one of India's great novelists, this story of one people's plight showcases the anxieties of a nation and the resistance of some to further marginalization.